Name Brands and Symbols Used Organic Products in the European Union and in Hungary - Szép, Attila (Acta Agraria Debreceniensis, 2004)
In 2002, the area which was monitored according to the requirements of organic farming numbered 103 thousand hectares in Hungary (this is some 1.7% of all cultivated land) and almost 1000 plants producing organic products were inspected. It is a realistic assumption, when considering these data, that within a short period time the area used for organic farming will reach the optimal 600.000 hectares.Contrary to overproduction in the EU – cereals, maize and other plants – organic products can be sold in unlimited quantities. Practice also indicates, that 90% of Hungarian certified organic products are sold in EU and Swiss markets.Thus, it is important to label Hungarian products according to EU standards. This way standard quality products can be sold easier and by increasing their income, manufacturers can contribute to the improvement of the environment.